THE ROLE OF CIVIL SOCIETY AND SOCIAL PARTNERSHIP IN THE DEVELOPMENT OF A DEMOCRATIC LEGAL STATE IN UZBEKISTAN (JOURNAL OF ANALYTICAL SYNERGY AND SCIENTIFIC HORIZON, 2025)
This article examines the evolution, essence, and institutional foundations of civil society and social partnership in Uzbekistan. It highlights the growing role of citizens’ self-governance bodies, particularly, the mahalla - within the political, social, and economic modernization processes of the country. The study analyses theoretical perspectives of national scholars, explores constructive and destructive forms of social participation, and evaluates Uzbekistan’s model of social partnership in comparison with international experiences. The article concludes by emphasizing the importance of civic engagement, legal culture, and cooperation among the state, non-governmental organizations, and citizens in building a democratic legal state.